KAZAKH SOURCES ON THE HISTORY OF RELATIONS BETWEEN THE KAZAKHS AND THE CENTRAL ASIAN KHANATES IN THE 18TH –THE FIRST HALF OF THE 19TH CENTURIES - Tulibayeva Zhuldyz Musaevna; Khairuldaeva Aisulu Madkasymovna (Scientific Journal of Pedagogy and Economics, 2019)
The article is devoted to the study of Kazakh sources on the history of relations between the Kazakhs and Bukhara, Kokand and Khiva khanates in the 18th - the first half of the 19th centuries. The source study review includes works of Kazakh poetic folklore containing original material on the studied problem. The authors pay special attention to the study of literary works Zar Zaman, which have survived to this day in written and oral form. The article made an attempt to objectively assess the information about the works of Kazakh akyns and zhyrau on the history of Kazakhs of the 18th - the first half of the 19th centuries, based on a historical analysis of the material identified. The authors concluded that the works of akyns and zhyrau are valuable and reliable sources for studying the history of relations between the Kazakhs and the Central Asian khanates and reflect the attitude of ordinary people to the events taking place in the Kazakh steppe. This article was prepared within the framework of a grant of the Ministry of Education and Science of the Republic of Kazakhstan aimed at funding basic and applied scientific research.